2009
DOI: 10.1007/s00701-009-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aneurysmal flow patterns and wall shear stresses calculated with computational flow dynamics in an anterior communicating artery aneurysm depend on knowledge of patient-specific inflow rates

Abstract: Intra-aneurysmal flow patterns and wall shear stress in an AcomA aneurysm calculated with computational flow dynamics depended strongly on the flow distribution between A1 segments. Patient-specific flow data measured with pcMRI obtained prior to computational flow dynamics are necessary for an accurate simulation of intra-aneurysmal flow patterns and calculation of wall shear stress in AcomA aneurysms. Further studies may indicate if wall shear stress calculated with computational flow dynamics can predict an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…As in previous studies, 8,13,24,36 bleb formation was significantly related to PCoA aneurysm rupture in the present study. In a recent study focusing on bleb formation in an effort to gain insight into the mechanisms underlying aneurysm rupture, the highest shear stress values were at or adjacent to the bleb formation.…”
Section: Projection Of Aneurysm and Bleb Formationsupporting
confidence: 89%
“…As in previous studies, 8,13,24,36 bleb formation was significantly related to PCoA aneurysm rupture in the present study. In a recent study focusing on bleb formation in an effort to gain insight into the mechanisms underlying aneurysm rupture, the highest shear stress values were at or adjacent to the bleb formation.…”
Section: Projection Of Aneurysm and Bleb Formationsupporting
confidence: 89%
“…These efforts resulted in the discovery that alternative morphometrics and IA hemodynamics correlate strongly with IA rupture. [7][8][9][10] We previously reported that size ratio (SR), IA size divided by parent vessel diameter, correlated strongly with IA rupture status (ruptured versus unruptured) in a retrospective review of patients presenting with IAs. 8 We also demonstrated that IA hemodynamics changed significantly with changes in SR, even when holding other IA morphometrics constant.…”
mentioning
confidence: 99%
“…Reliable patient-specific boundary conditions for CFD in patients with both ruptured and unruptured aneurysms are needed to predict local hemodynamics more accurately in intracranial aneurysms. 6,7 Accurate BFV measurements in the perianeurysmal arteries in the circle of Willis are difficult to obtain, because the skull and the tortuosity of the arteries impede conventional methodologies, such as TCD. Making use of phase-contrast MR imaging enables BFV measurement at targeted arterial locations, provided that the resolution is sufficiently high.…”
mentioning
confidence: 99%